2011
DOI: 10.1007/s10693-011-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Did Good Corporate Governance Improve Bank Performance during the Financial Crisis?

Abstract: This paper focuses on the effects of corporate governance on bank performance during the financial crisis of 2008. Using data on large publicly traded U.S. banks, we examine whether banks with stronger corporate governance mechanisms were associated with higher profitability and better stock market performance amidst the crisis. Our empirical findings on the effects of corporate governance on bank performance are mixed. Although the results suggest that banks with stronger corporate governance mechanisms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(94 citation statements)
references
References 34 publications
9
82
1
2
Order By: Relevance
“…However, corporate governance optimistically acts as an excellent mechanism during the financial crisis to minimize non-performing loan and keep banks stable financially and efficiently as the coefficients of CG*GFC are positive for stability (LNZ) and stability efficiency (SE) and negative for a non-performing loan to total loans (NPLTL). But unfortunately, contrary to our hypothesis and findings of Peni and Vähämaa (2012) corporate governance cannot be a significant determinant of bank performance during the crisis in a developing economy like Bangladesh. While financial freedom (FF) is also an insignificant determinant for bank performance and risk-taking as there is no significant relationship between them, as it could be explained as Bangladeshi financial sector is mostly restricted and therefore, it is yet to open the financial market.…”
Section: The Linear and Non-linear Effect Of Corporate Governancecontrasting
confidence: 99%
See 3 more Smart Citations
“…However, corporate governance optimistically acts as an excellent mechanism during the financial crisis to minimize non-performing loan and keep banks stable financially and efficiently as the coefficients of CG*GFC are positive for stability (LNZ) and stability efficiency (SE) and negative for a non-performing loan to total loans (NPLTL). But unfortunately, contrary to our hypothesis and findings of Peni and Vähämaa (2012) corporate governance cannot be a significant determinant of bank performance during the crisis in a developing economy like Bangladesh. While financial freedom (FF) is also an insignificant determinant for bank performance and risk-taking as there is no significant relationship between them, as it could be explained as Bangladeshi financial sector is mostly restricted and therefore, it is yet to open the financial market.…”
Section: The Linear and Non-linear Effect Of Corporate Governancecontrasting
confidence: 99%
“…But little evidence found that extend the relationship between bank risk and performance together in corporate governance literature, for example, Peni and Vähämaa (2012).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the view that boards pushed banks to engage in business strategies that were valued highly by shareholders before the crisis and turned out to be a source of weakness ex post. Similarly, Peni and Vähämaa (2012) document a negative association between strong governance mechanisms and stock market valuations for U.S. banks in 2008. In the immediate aftermath of the crisis, the association turned positive, however.…”
Section: Introductionmentioning
confidence: 96%